1990
DOI: 10.1080/10402009008981999
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Attack of Perfluorinated Alkyl Ether Lubricant Molecules by Metal Oxide Surfaces

Abstract: N a t i o n a l A e r o n a u t i c s and Space A d m i n i s t r a t i o nLewis Research Center C l e v e l a n d , O h i o 44135 SUMMARYThe r e a c t i o n s o f l i n e a r p e r f l u o r o p o l y a l k y l e t h e r (PFAE) l u b r i c a n t s w i t h a-FezO3 and Fe203-based s o l i d s u p e r a c i d s were s t u d i e d . a-Fe2O3 proceeds i n two s t a g e s . The first s t a g e i s an i n i t i a l slow c a t a l y t i c d e c o m p o s i t i o n o f t h e f l u i d . T h i s r e a c t i o n r e l e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…It is well known that, in the presence of metal and metal oxide, the rapid degradation of PFPEs takes place at temperatures below their decomposition temperatures [21,22]. So, far, two different mechanisms have been reported: one is the decomposition caused by Lewis acid sites, [23,24] the other is the decomposition caused by nonLewis acid sites [25,26]. Suzuki and Kennedy [27] found that the flash temperature generated at the head/disk interface for an Al 2 O 3 -TiC slider on a rigid thin film magnetic disk is about 150 ∘ C under 1 N impact load.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that, in the presence of metal and metal oxide, the rapid degradation of PFPEs takes place at temperatures below their decomposition temperatures [21,22]. So, far, two different mechanisms have been reported: one is the decomposition caused by Lewis acid sites, [23,24] the other is the decomposition caused by nonLewis acid sites [25,26]. Suzuki and Kennedy [27] found that the flash temperature generated at the head/disk interface for an Al 2 O 3 -TiC slider on a rigid thin film magnetic disk is about 150 ∘ C under 1 N impact load.…”
Section: Introductionmentioning
confidence: 99%
“…A two-step fluid decomposition process has been proposed [6,8,15]: conversion of the metal surface to a metal fluoride which functions as a Lewis acid site; and catalytic decomposition of the fluid by interaction with these Lewis acid sites. A critical step that precedes this two-step process is the degradation of the PFPAE fluid due to either (i) the metal reactivity with the PFPAE fluid at high temperatures in a static environment or (ii) in a tribological environment at asperity contacts where the localized temperature and shear stresses are at a maximum.…”
Section: Problems With Pfpae Fluidsmentioning
confidence: 99%
“…Comparing hydrocarbon chemistry in oxidative environments, hydrocarbons have the tendency to form water and OH radicals via a free radical process. This situation does not apply to perfluorinated compounds due to the resistance of the C-F bond to the attack by free radicals and the thermodynamic instability of OF 2 and OF species [6,7]. This renders PFPAEs JOURNAL OF SYNTHETIC LUBRICATION…”
mentioning
confidence: 93%
“…The iat r=0 is -Itlen as -v (19) The velocities Uc and U,, gre gc!ud~ hle rate of cooling and heating at the condenser and evaoraive sion. gr6 h te schermtic of a simple mode!…”
Section: -10mentioning
confidence: 99%
“…19,7]. We chose to use one of these chaotic time series for comparability with prior works and availability of data.…”
Section: The Mackey-glass Equationmentioning
confidence: 99%